Comprehensive Multiple-Choice Questions in Pathology A Study Guide - Kohli, Vinay Kumar; Kohli, Chitra; Singh, Akanksha; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book concisely provides important Pathology concepts to aid pathology trainees, including medical students and resident physicians, in passing any advanced pathology examination. It provides a much needed revision aid and study guide. Through dedicated questions and answers over 23 chapters covering every major organ system, the book will develop skills needed to deal with different aspects of pathology in a systematic yet summarized manner. The book helps solve problems faced by trainees by providing the highest yield content. Throughout the book, an intuitive and systematic approach is used to reinforce fundamental concepts.
Cellular Pathology, Inflammation And Repair -- Genetic Disorders -- Immune System Disorders -- Neoplastic Disorders -- Infectious Diseases -- Blood Vessels -- The Heart -- Hematopathology Of Red Blood Cells And White Blood Cells -- Lungs -- Head And Neck -- Gastrointestinal Tract -- Liver And Biliary Tract -- Pancreas -- Kidney -- Male Genital Tract -- Female Genital Tract -- Breast -- Endocrine System -- Skin Disorders -- Bone, Joints And Soft Tissue Disorders -- Peripheral Nerves & Skeletal Muscles -- Central Nervous System -- The Eye.
Keywords: Pathology; Pathology; Pathology; Examination Question